Supporting adherence for people starting a new medication for a long-term condition through community pharmacies: a pragmatic randomised controlled trial of the New Medicine Service. Issue 10 (8th December 2015) - Elliott, Rachel Ann; Boyd, Matthew J; Salema, Nde-Eshimuni; Davies, James; Barber, Nicholas; Mehta, Rajnikant Laxmishanker; Tanajewski, Lukasz; Waring, Justin; Latif, Asam; Gkountouras, Georgios; Avery, A J; Chuter, Antony; et al.
Abstract : Objective: To examine the effectiveness of the New Medicine Service (NMS), a national community pharmacy service to support medicines-taking in people starting a new medicine for a long-term condition, compared with normal practice. Methods: Pragmatic patient-level parallel randomised controlled trial, in 46 community pharmacies in England. Patients 1:1 block randomisation stratified by drug/disease group within each pharmacy. 504 participants (NMS: 251) aged 14 years and over, identified in the pharmacy on presentation of a prescription for asthma/chronic obstructive pulmonary disease, hypertension, type 2 diabetes or an anticoagulant/antiplatelet agent. NMS intervention: One consultation 7–14 days after presentation of prescription followed by another 14–21 days thereafter to identify problems with treatment and provide support if needed. Controls received normal practice. Adherence, defined as missing no doses without the advice of a medical professional in the previous 7 days, was assessed through patient self-report at 10 weeks. Intention-to-treat analysis was employed, with outcome adjusted for recruiting pharmacy, NMS disease category, age, sex and medication count. Cost to the National Health Service (NHS) was collected. Results: At 10 weeks, 53 patients had withdrawn and 443 (85%) patients were contacted successfully by telephone. In the unadjusted analysis of 378 patients still taking the initial medicine, 61% (95% CI 54% to 67%) and 71% (95% CI 64% to 77%) patients were adherent in the normal practice and NMS arms, respectively (p=0.04 for difference). In the adjusted intention-to-treat analysis, the OR for increased adherence was 1.67 (95% CI 1.06 to 2.62; p=0.027) in favour of the NMS arm. There was a general trend to reduced NHS costs, albeit, statistically non-significant, for the NMS intervention: saving £21 (95% CI −£59 to £100, p=0.128) per patient. Conclusions: The NMS significantly increased the proportion of patients adhering to their new medicine by about 10%, compared with normal practice. Trial registration numbers: ClinicalTrials.gov trial reference number NCT01635361 (http://clinicaltrials.gov/ct2/show/NCT01635361 ). Current Controlled trials: trial reference number ISRCTN 23560818 (http://www.controlled-trials.com/ISRCTN23560818/ ; DOI 10.1186/ISRCTN23560818 ). UK Clinical Research Network (UKCRN) study 12494 (http://public.ukcrn.org.uk/Search/StudyDetail.aspx?StudyID=12494 ).